THE IMPACT OF EDUCATIONAL TECHNOLOGIES BASED ON MOTOR COORDINATION AND MULTIMODAL INTEGRATION ON THE FORMATION OF MUSICAL-PERFORMANCE COMPETENCIES IN STUDENTS OF GRADES 5–7 - Shermatova Xilola (Ecomind Press, 2026)
The modernization of contemporary music education requires the integration of innovative pedagogical approaches aimed at developing students’ practical performance competencies. This study examines the impact of educational technologies based on motor coordination and multimodal integration on the formation of musical-performance competencies among students in grades 5–7. The research is grounded in the interdisciplinary interaction of pedagogy, psychology, neuroscience, and music methodology, emphasizing the role of embodied learning and multisensory engagement in performance development. The study substantiates the theoretical and methodological foundations of motor coordination as a psychomotor mechanism supporting rhythmic accuracy, expressive articulation, and interpretative awareness. Multimodal learning, incorporating auditory, visual, and kinesthetic modalities, is presented as a pedagogically effective framework for enhancing students’ performance skills. The experimental component of the research demonstrates that the integration of movement-based exercises, digital tools, and collaborative performance activities contributes to measurable improvements in coordination, rhythmic stability, and expressive interpretation. The findings confirm that educational technologies grounded in motor coordination and multimodal integration significantly enhance students’ musical-performance competencies and motivation toward music learning. The proposed methodological model provides practical implications for music educators and curriculum designers and contributes to the advancement of competency-based and performance-oriented music education.
Keywords: Motor coordination; multimodal integration; music education; musical-performance competencies; psychomotor development; middle school students; rhythm training; embodied learning; competency-based education; sensory integration; performance pedagogy; interactive learning technologies; music methodology; creative performance; educational innovation.